RUSSIAN OPEN EDUCATIONAL RESOURCES AND MASSIVE ONLINE COURSES - Alexander A. Andreev (Moscow Polytechnic University, 2016)
The article views the organizational and pedagogical characteristics of the Russianopen educational resources and massive open online courses. The author adduces the basic characteristics of xMOOC such as fair use, free will, multitude of students, using of diverse Internet services, accent on self-dependent work, self-control and mutual control. The Russian priority in this area is proved.